Food protein-induced enterocolitis syndrome – a little-known form of non-IgE-mediated food hypersensitivity - Skiba, Anna; Boznański, Andrzej (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Food protein-induced enterocolitis syndrome (FPIES) is a presentation of non-IgE-mediated food allergy and is probably more common than is currently diagnosed. Epidemiological data that estimate the prevalence of this disease are limited. In infancy it is usually induced by cow’s milk protein, rice, and soybean; in older children and adults fish and seashell may be the triggering factors. It is characterised by the presence of vomiting and diarrhoea that can lead to dehydration, lethargy, pallor, and metabolic acidosis. Chronic FPIES usually presents as failure to thrive. The diagnosis is based on clinical criteria. Potential cases can be misdiagnosed as more common paediatric illnesses, such as gastroenteritis or sepsis. Treatment consists of education and avoidance of the offending foods. In 2017 international guidelines for the diagnosis and management of FPIES were published [1]. This article contains current information on food protein-induced enterocolitis syndrome.